Enhancing Economic Empowerment through Productive Zakat: A Case Study of Coastal Communities Cak Kaji Program by BAZNAS, Indonesia - ZA, Moh. Ah. Subhan; Wirasabda, Miftahal Anjar; Marpuah, Siti; Ritonga, Iskandar (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This study explores the role of productive zakat in fostering sustainable economic empowerment among coastal communities, using the Cak Kaji Program implemented by the National Board of Zakat (BAZNAS) in Gresik, Indonesia. The research examines how zakat, as a core instrument in Islamic economics, can transcend traditional charitable functions and contribute to long-term socioeconomic development. The result is the empowerment through several programs, namely rolling livestock, micro finance and rombong assistance for small seller. This study it can be concluded that the community empowerment program through the distribution of productive zakat carried out by Baznas Gresik is already good, where Baznas Gresik has provided alternative livelihoods, capital access, technology access, markets access, and the collective action development. But there is something that needs to be improved in alternative livelihoods and access to markets. Baznas Gresik needs to add types of empowerment programs so that there are more choices for mustahiq businesses and create a market for the results of mustahiq businesses so that they can be well absorbed by consumers. The study contributes to the broader discourse on the operationalization of Islamic economic principles in contemporary development frameworks, offering insights for policymakers, zakat institutions, and development practitioners worldwide.